The versatile roles of odontogenic ameloblast-associated protein in odontogenesis, junctional epithelium regeneration and periodontal disease - Zhu, Sipin; Xiang, Chuan; Charlesworth, Oscar; Bennett, Samuel; Zhang, Sijuan; Zhou, Maio; Kujan, Omar; Xu, Jiake (Frontiers in Physiology, 2022)
Junctional epithelium (JE) is a vital epithelial component which forms an attachment to the tooth surface at the gingival sulcus by the adhesion of protein complexes from its basal layer. Disruption of the JE is associated with the development of gingivitis, periodontal disease, and alveolar bone loss. Odontogenic ameloblast-associated (ODAM) is comprised of a signal peptide and an ODAM protein with 12 putative glycosylation sites. It is expressed during odontogenesis by maturation stage ameloblasts and is incorporated into the enamel matrix during the formation of outer and surface layer enamel. ODAM, as a secreted protein which is accumulated at the interface between basal lamina and enamel, mediates the adhesion of the JE to the tooth surface; and is involved with extracellular signalling of WNT and ARHGEF5-RhoA, as well as intracellular signalling of BMP-2-BMPR-IB-ODAM. ODAM is also found to be highly expressed in salivary glands and appears to have implications for the regulation of formation, repair, and regeneration of the JE. Bioinformatics and research data have identified the anti-cancer properties of ODAM, indicating its potential both as a prognostic biomarker and therapeutic target. Understanding the biology of ODAM will help to design therapeutic strategies for periodontal and dental disorders.